Interwencja bogini/Szatana? "Wenus w futrze" (2013) – lektura palimpsestowa filmu Romana Polańskiego - Iwona Kolasińska-Pasterczyk (Załącznik Kulturoznawczy)
The text concerns Roman Polanski’s film Venus in Fur (2013), a multi-layer psychodrama written for two characters, taking place on several levels of human relations: actress vs. director, literary character vs. performing artist, man vs. woman. Venus in Fur has been defined as a kind of palimpsest, i.e. a film story based on the fictional skeleton of other works. Referring to the concept developed by Gérard Genette, who categorized the ways in which different texts interact with each other, the article investigates the film’s hypertextuality, i.e. the “grafting” of Venus in Fur (as a hypertext) upon earlier works (hypotexts). When discussing Venus in Fur as a text of culture constituting a hypertext superimposed on other literary pieces, such as David Ives’ dramas, Leopold von Sacher-Masoch’s novels, mythological and biblical stories, it was necessary to identify their mutual relations by deciphering all the interconnections, reworkings, reinterpretations, and revisions. Due to the relationships existing between the various cultural texts in the film, the analysis was treated as a palimpsest reading. Attention was also paid to the director-actress relationship and the role of the female character in connection with the reinterpretation of the myth of the goddess Venus.